Homogeneously Distributed NiFe Alloy Nanoparticles on 3D Carbon Fiber Network as a Bifunctional Electrocatalyst for Overall Water Splitting. Issue 9 (7th May 2019) - Lv, Yanlong; Batool, Aisha; Wei, Yuxuan; Xin, Qi; Boddula, Rajender; Jan, Saad Ullah; Akram, Muhammad Zain; Tian, Liangqiu; Guo, Beidou; Gong, Jian Ru
Abstract: Overall water splitting is a promising way to alleviate the energy crisis by producing renewable and clean hydrogen fuel. The development of highly efficient, low cost, and stable electrocatalysts is of great importance for the large‐scale application of overall water splitting. Herein, we report an effective and facile strategy to prepare non‐noble nickel‐iron (NiFe) alloy nanoparticles (NPs) decorated on oxidized carbon cloth (OCC) as a bifunctional electrocatalyst for overall water splitting. The homogeneous dispersion of small‐sized NPs achieved by anchoring the metal species to oxygen‐containing groups on the OCC support, together with the 3D conductive nature of the scaffold, ensures optimal exposure of active metal sites and also results in high electrical conductivity. As a result, our electrocatalyst affords superior oxygen evolution reaction activity with a low overpotential of 281 mV at 10 mA cm −2 and is also stable for up to around 17 h in an alkaline electrolyte; the catalyst also demonstrates a high efficiency for overall water splitting. Our strategy has, therefore, great potential for practical energy conversion applications. Abstract : Anchored down : An effective strategy is developed by decorating NiFe alloy nanoparticles on a 3D oxidized carbon network. The homogeneous dispersion and small size of the alloy nanoparticles achieved by anchoring the metal species to oxygen‐containing groups, together with the 3D conductive scaffold, ensure optimal exposure of active metal sites and high electrical conductivity of the electrocatalyst for excellent overall water splitting performance.